EDITORIAL - Aykara, Thomas (Journal of Dharma, 1980)
Is it inevitable that man should articulate his experience of the deeper dimensions of the Real in terms of those realities which are intimate to him in his own self? Man measures his power to work by reference to the power he experiences in his own muscles or in those of a stallion. So, too, he tries to understand the felt need for God in his own being in terms of his own constitutive spiritual powers. For Feuerbach God is the sum total of all the auspicious perfections such as being, knowing and willing in man projected into infinity. Though, for St. Thomas Aquinas, God is not a projection of the spiritual essence of men into infinity, He is to be known in analogical terms with the perfections found in man and nature. Thus God is said to be fullness of Being, consciousness and Bliss (Saccidananta).